Scaling the CERN OpenStack cloud. Issue 1 (December 2015) - Bell, T; Bompastor, B; Bukowiec, S; Castro Leon, J; Denis, M K; van Eldik, J; Lobo, M Fermin; Alvarez, L Fernandez; Rodriguez, D Fernandez; Marino, A; Moreira, B; Noel, B; et al.
Abstract: CERN has been running a production OpenStack cloud since July 2013 to support physics computing and infrastructure services for the site. In the past year, CERN Cloud Infrastructure has seen a constant increase in nodes, virtual machines, users and projects. This paper will present what has been done in order to make the CERN cloud infrastructure scale out.